Wild and semi-wild edible plants used by the communities of Acholi sub-region, Northern Uganda - Nyero, Alfred; Achaye, Innocent; Odongo, Walter; Anywar, Godwin; Malinga, Geoffrey Maxwell (Ethnobotany Research and Applications, 2021)
Background: In the Acholi sub-region, consumption of wild edible plants is still an integral part of the food culture, particularly during times of food shortage. However, much of indigenous traditional knowledge has not been documented due to the history of prolonged civil war in the area. We conducted an ethnobotanical survey to document the wild plants utilized by the Acholi communities in northern Uganda. Methods: Data was collected using semi-structured questionnaires administered to 1,353 respondents between November 2017 and February 2018 and 65 focus group discussions. Results: Seventy-three edible plants from 39 families were identified to species level while three species were unidentified. Vitex doniana (0.72), Aframomum alboviolaceum. (0.70), Saba comorensis (0.45), Hibiscus surattensis (0.42), and Borassus aethiopum (0.39) had the highest relative frequencies of citation. Fabaceae (7) and Euphorbiaceae (5) had the highest number of plant species. Most of the edible plants were herbs (34%) and trees (31%). Fruits were the major parts consumed (57%), followed by leaves (37%). Only 34% of species were cooked before eating, while 60% were eaten raw. Sixty-seven percent of the species were harvested during the rainy season and 22% in the dry season. Conclusion: There is a rich diversity of wild edible plants in the Acholi sub-region. Conservation and domestication of these plants will provide a buffer crop and enhance the food security of the locals in the face of recurrent droughts and climate change. Keywords: Wild edible plants, Indigenous knowledge Ethnobotany, Food security.